One hundred years of solitude ended: A second species of Marmasoma White, 1916 (Diptera, Bombyliidae, Bombyliinae, Eclimini) from Australia - Li, Xuankun; Yeates, David K. (Zootaxa, 2018)
Known as a monotypic genus for over a century, Marmasoma White, 1916 is an endemic Australian bee fly genus belonging to the tribe Eclimini of the subfamily Bombyliinae. A new species: Marmasoma hortorum sp. nov. is described based on a series of specimens from Western Australia and South Australia. This new species can be easily distinguished from the congener by the inconspicuous pale wing markings and mostly white to pale yellow scales on the body, as well as characters of both male and female genitalia. M. sumptuosum is found in south-eastern Australia, including Tasmania, and some specimens have been collected on Kangaroo Island, South Australia. M. hortorum sp. nov. occurs in south Western Australia, and a pair of specimens has been taken just north of Port Augusta in South Australia. A key to species of Marmasoma is provided.